Photo-cross-linkable polymeric optoelectronics based on the [2 + 2] cycloaddition reaction of cinnamic acid - Schelkle, Korwin; Bender, Markus; Beck, Sebastian; Jeltsch, Krischan F.; Stolz, Sebastian; Zimmermann, Johannes; Weitz, R. Thomas; Pucci, Annemarie; Müllen, Klaus; Hamburger, Manuel; Bunz, Uwe H. F. (Macromolecules, 2016)
We report the synthesis of cinnamic acid-functionalized conjugated polymers, which are cross-linked via [2 + 2] cycloaddition by UV illumination, reducing their solubility. The cross-linking reaction was investigated by a combination of FTIR and optical spectroscopy, and an optimum condition for the solubility modulation of thin films, a major challenge in the solution-phase fabrication of layered optoelectronic devices, was reached. As proof of concept, OLEDs were fabricated, using these conjugated polymers as emissive layers.
Gesehen am 13.05.2020